2010
DOI: 10.1007/s10875-010-9461-y
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Common Genetic Variants in Pre-microRNAs in Patients with Ulcerative Colitis

Abstract: Our results provided the first evidence that rs3746444 SNP may influence the susceptibility to UC, and both rs3746444 and rs11614913 SNPs may influence the pathophysiological features of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 20 publications
1
45
1
6
Order By: Relevance
“…Guo et al demonstrated that the GG genotype was associated with increased esophageal squamous cell carcinoma risk, particularly among smokers (37). C allele carriers were reported to be susceptible to gastric cancer in a Japanese population (38), while the C allele was found to be protective against gastric cancer in a Chinese population (24). Inconsistent results of the association between the rs2910164 miR-146a genotype and cancer risk may represent distinct heterogeneous etiology in different tumor types or differences in the ethnicity of investigated populations.…”
Section: A B C D E F Gmentioning
confidence: 99%
“…Guo et al demonstrated that the GG genotype was associated with increased esophageal squamous cell carcinoma risk, particularly among smokers (37). C allele carriers were reported to be susceptible to gastric cancer in a Japanese population (38), while the C allele was found to be protective against gastric cancer in a Chinese population (24). Inconsistent results of the association between the rs2910164 miR-146a genotype and cancer risk may represent distinct heterogeneous etiology in different tumor types or differences in the ethnicity of investigated populations.…”
Section: A B C D E F Gmentioning
confidence: 99%
“…miRNAs have been indicated to play key roles in many cellular processes, including development, differentiation, proliferation, maturation and apoptosis [20][21][22][23]. In recent years, researchers are exploring the role of miRNAs on the pathogenesis of IBD from multiple perspectives [24], including different expression of miRNAs in local intestinal tissues of IBD [25], miRNAs in the blood serum of UC patients [26] and correlation between miRNA single nucleotide polymorphism (SNP) and IBD [27]. By investigating the expression of miRNAs in various colon tissues including those with UC, Wu et al observed a variety of downregulated miRNAs, including miR-192, miR-375 and miR-422b [25].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 41 patients exhibited extensions of the inflammatory mucosae into proximal sites (the transverse and ascending colons and the cecum). This cohort was recruited from our previous studies that investigated the associations of DNA methylation with clinical phenotypes, host genetic factors and telomere lengths [28,[36][37][38]. This study was approved by the Human Research Ethics Committee of the Fujita Health University School of Medicine.…”
Section: Tissue Samplesmentioning
confidence: 99%